Representation of Sustainable Development Goals in an Indonesian EFL Textbook - Khoiru Nisa Atika; Alief Noor Farida (Universitas Lambung Mangkurat, 2026)
This study identifies the Sustainable Development Goals (SDGs) represented in textbooks and analyzes how these goals are implemented in learning activities and task instructions. This study fills a gap in previous research by presenting an analysis that focuses on SDGs integrated through learning activities and task instructions in the English for Nusantara textbook for eighth grade. By shifting the focus from simply analyzing the existence of content to its pedagogical practice, this study makes a new contribution to the study of English as a Foreign Language (EFL) textbooks and Education for Sustainable Development (ESD). Therefore, the results of this study are expected to enrich theoretical studies and provide practical implications as part of efforts to align English as a Foreign Language (EFL) education with Sustainable Development Goal (SDG) 4.7. Through this analysis, this study aims to evaluate the role of textbooks in providing a means for meaningful Sustainable Education at the secondary education level in Indonesia. This study uses a qualitative research design to analyze the representation and pedagogical integration of Sustainable Development Goals (SDGs) using a qualitative content analysis approach in English as a Foreign Language (EFL) textbooks.